2007
DOI: 10.1029/2005jc002893
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐shore sediment transport on natural beaches and its relation to sandbar migration patterns: 1. Field observations and derivation of a transport parameterization

Abstract: [1] Cross-shore sediment transport processes are investigated with measurements of horizontal velocity and sediment suspension obtained with electromagnetic current meters and optical backscatter sensors on five different beaches across Europe. Data were gathered under a wide variety of hydrodynamic and morphological conditions spanning the swash, surf, and shoaling zones. Results show that the near bed velocity moments, normalized by the local energy level (hu t 2 i n ), have consistent shapes (shape function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 42 publications
4
47
0
1
Order By: Relevance
“…Maximum values of flow velocity skewness have been reported from the wave breaker zone (Doering and Bowen, 1987) and this has subsequently been linked to sediment transport. Roelvink and Stive (1989) found that flow skewness provided a significant contribution to the transport, while Thornton et al (1996), Russell and Huntley (1999) and Marino-Tapia et al (2007) demonstrate in the field that the dominant transport mechanism outside the surf zone is onshore transport due to flow velocity skewness.…”
Section: Introductionmentioning
confidence: 93%
“…Maximum values of flow velocity skewness have been reported from the wave breaker zone (Doering and Bowen, 1987) and this has subsequently been linked to sediment transport. Roelvink and Stive (1989) found that flow skewness provided a significant contribution to the transport, while Thornton et al (1996), Russell and Huntley (1999) and Marino-Tapia et al (2007) demonstrate in the field that the dominant transport mechanism outside the surf zone is onshore transport due to flow velocity skewness.…”
Section: Introductionmentioning
confidence: 93%
“…In the last twenty years there has been a significant increase in the number of studies on the swash zone. Nowadays, there are different studies that deal with the terms that play a role in the dynamic at the swash zone: bore collapsing (Puleo et al 2000, Jackson et al 2004Aagard and Hughes 2006), backwash Mason 1994 or Butt andRussell 1999), advection (Jackson et al 2004 or Alsina et al 2009), infiltration/ex-filtration effects Nielsen 1997, Elfrink andBaldock 2002;Baldock and Nielsen 2010), asymmetries in velocity or acceleration (Roelvink and Stive 1989, Mariño-Tapia et al 2007, Houser and Barret, 2010Pedrozo-Acuña et al 2011), long wave and wave groups (Baldock et al 2011), etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that mean offshore-directed flows are responsible for beach erosion and offshore bar migration under energetic wave conditions, but there is considerable debate in the literature as to what causes beach accretion and onshore bar migration under calm wave conditions. There have been a number of processes proposed that may be implicated in onshore sediment transport, berm construction and bar migration, including: (1) onshore mass flux due to cell circulation (Aagaard et al, 2006); (2) sediment stratification (Conley et al, 2008); (3) turbulence associated with breaking waves and bores (Butt et al, 2004); (4) cross-shore velocity skewness ('wave skewness'; Marino-Tapia et al, 2007); (5) cross-shore velocity acceleration skewness ('wave asymmetry'; Hoefel and Elgar, 2003); (6) ventilated boundary layer (Conley and Inman, 1992); and (7) plug flow due to horizontal pressure gradients (Foster et al, 2006). These different processes are not necessarily mutually exclusive and all, except (1), are addressed during BARDEX II.…”
Section: Introductionmentioning
confidence: 99%